Peningkatan Kinerja Layanan dan Pengolahan Data Perangkat Desa Ulak Kembahang Melalui Pelatihan Aplikasi Komputer Ekonomi dan Bisnis - Imelda; Yuniarti, Emylia; Febrina, Shelly; Novi Yarsah, Waldi; Teguh, Muhammad (UNIB Press, 2024)
The model of community service activities (PKM) is assistance in the form of technical guidance with direct practice in the Economics and Business Application Laboratory through the MS. Word and MS. Excel. PKM participants were 25 people, namely village officials including representatives of the Village Government, Village Representative Council (BPD), Community Empowerment Agency (LPM), PKK and Posyandu administrators and Youth Organization, Service activities in collaboration with the Economics and Business Application Laboratory. The results of the activity evaluation show that the average skills of 74.5 percent of participants are skilled and 20.5 percent are quite skilled for 8 statement items about skills using MS. Word, MS Excell, MS Power Point, creating Gmail and saving files on G-Drive.